Iron Curtain: The Crushing of Eastern Europe, 1944-1956 - Applebaum, Anne (Knopf Doubleday Publishing Group, 2013)
National Book Award Finalist TIME Magazine's #1 Nonfiction Book of 2012A New York Times Notable BookA Washington Post Top Ten Book of 2012Best Nonfiction of 2012: The Wall Street Journal, The Plain Dealer In the much-anticipated follow-up to her Pulitzer Prize-winning Gulag, acclaimed journalist Anne Applebaum delivers a groundbreaking history of how Communism took over Eastern Europe after World War II and transformed in frightening fashion the individuals who came under its sway. Iron Curtain describes how, spurred by Stalin and his secret police, the Communist regimes of Eastern Europe were created and what daily life was like once they were complete. Drawing on newly opened East European archives, interviews, and personal accounts translated for the first time, Applebaum portrays in chilling detail the dilemmas faced by millions of individuals trying to adjust to a way of life that challenged their every belief and took away everything they had accumulated. As a result the Soviet Bloc became a lost civilization, one whose cruelty, paranoia, bizarre morality, and strange aesthetics Applebaum captures in these electrifying pages.
Keywords: References - Boel et al. (2021); Archives and Human Rights

René Cassin and Human Rights: From the Great War to the Universal Declaration - Winter, Jay; Prost, Antoine (Cambridge University Press, 2013)
Through the life of one extraordinary man, this biography reveals what the term human rights meant to the men and women who endured two world wars, and how this major political and intellectual movement ultimately inspired and enshrined the Universal Declaration of Human Rights. René Cassin was a man of his generation, committed to moving from war to peace through international law, and whose work won him the Nobel Peace Prize in 1968. His life crossed all the major events of the first seventy years of the twentieth century, and illustrates the hopes, aspirations, failures and achievements of an entire generation. It shows how today's human rights regimes emerged from the First World War as a pacifist response to that catastrophe and how, after 1945, human rights became a way to go beyond the dangers of absolute state sovereignty, helping to create today's European project.
Keywords: References - Comma (2020 1-2); Archives and Human Rights